2016
DOI: 10.1080/14756366.2016.1222584
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and evaluation of 3-quinoline carboxylic acids as new inhibitors of protein kinase CK2

Abstract: In this article, the derivatives of 3-quinoline carboxylic acid were studied as inhibitors of protein kinase CK2. Forty-three new compounds were synthesized. Among them 22 compounds inhibiting CK2 with IC 50 in the range from 0.65 to 18.2 mM were identified. The most active inhibitors were found among tetrazolo-quinoline-4-carboxylic acid and 2-aminoquinoline-3-carboxylic acid derivatives. KeywordsInhibitor, protein kinase CK2, tetrazolo[1,5-a]quinoline-4-carboxylic acid, 2-aminoquinoline-3-carboxylic acid, 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The receptor was prepared using MGL Tools and AutoGrid [24]. We have used docking parameters reported earlier [26]. They are shown in table 1.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…The receptor was prepared using MGL Tools and AutoGrid [24]. We have used docking parameters reported earlier [26]. They are shown in table 1.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…As we all know, carboxylic acids (RCOOH) can often be used to synthetize all kinds of products, such as polymers, pharmaceuticals [ 1 ] (Scheme 1), solvent, and food additives. Along with the development of science and technology, many kinds of carboxylic acids have been produced industrially on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…

Novel quinoline derivatives carrying nitrones and oxime as nitric oxide donors were prepared and characterized using different spectroscopic techniques. Several mechanisms can explain the anticancer effect of quinoline derivatives including: topoisomerase inhibition, [21][22][23] DNA intercalation, [24] protein kinases inhibition, [25][26][27] tubulin polymerase inhibition, [28][29][30][31] and induction of apoptosis. Antiproliferative screening results showed that the 2-benzylthioquinoline nitrones 6e and 6f and the 2-methylthio analogues 6g and 6h exhibited promising antiproliferative activity especially against leukemia and colon cancer cell lines.

…”
mentioning
confidence: 99%